Cash Waqf Linked Deposit in Indonesia: A Conceptual and Legal Review - Elis Nurhasanah; Khotibul Umam; Andi Amri (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
This research aims to examine Cash Waqf Linked Deposit (CWLD) within the context of Indonesia’s Islamic finance industry, with a focus on its principles, regulatory framework, and implementation challenges. Although CWLD has recently been introduced as an innovative financial instrument, legal and conceptual studies on the topic remain limited, particularly within the scope of national regulations. This study adopts a qualitative method with a descriptive-analytical approach. Data were obtained from Law No. 41 of 2004 on Waqf, Government Regulation No. 25 of 2018, relevant fatwas issued by the Indonesian Ulema Council, and academic literature. The findings indicate that CWLD integrates cash waqf with sharia-compliant deposit products. The collected waqf funds are placed in deposits, and the returns are allocated to social programs and economic empowerment initiatives. However, CWLD implementation faces several challenges, including the absence of specific regulations and low levels of public awareness. This study concludes that CWLD has significant potential to strengthen the waqf ecosystem and promote Islamic financial inclusion. To optimize its role in socio-economic development, regulatory support, public education, and cross-agency collaboration are essential.